Peningkatan Kemampuan dalam Pembuatan Laporan Keuangan dan Online Marketing untuk Meningkatkan Kesejahteraan UMKM - Safrida, Lili; Anisah, Hastin Umi; Limarjan, Sustinah; Rasidah, Rasidah; Hardi, Enny; Novriyandana, Rifqi; Amalia, Wia Rizqi (Carmin: Journal of Community Service, 2024)
This Community Service Program (PkM) aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Kuin Utara Tourism Village, Banjarmasin, which has been designated as one of the 75 best tourism villages in Indonesia. Through training in financial reporting and online marketing, it is expected that MSMEs can improve financial management, increase sales, and competitiveness in the market. Initial results show high participation from MSMEs in the training activities. This study will analyze the impact of the training on improving the knowledge, skills, and performance of MSMEs, as well as identifying the challenges faced in implementing the program. The PkM is designed in several stages, with the PkM activities agenda being carried out from May 2024 to December 2024. The training location is held in the Kuin Utara sub-district, Banjarmasin City, specifically at the residence of one of the MSMEs around the Sultan Suriansyah Tomb. The learning media used by partners is Android-based smartphones with active data packages and assistance from the PkM team. The training is conducted in one location so that the team and partners can interact more easily. The training was attended by 46 participants and was consistent in the evaluation process. As a result, MSMEs have gained increased skills, improved financial management, and increased sales and revenue.